The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/w9010030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water Scarcity on the Fenhe River Basin and Mitigation Strategies

Abstract: This study produced a drought map for the Fenhe River basin covering the period from 150 BC to 2012 using regional historical drought records. Based on meteorological and hydrological features, the characteristics and causes of water scarcity in the Fenhe River basin were examined, along with their impact on the national economy and ecological environment. The effects of water scarcity in the basin on the national economy were determined from agricultural, industrial, and domestic perspectives. The impact on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Results in Table 3 indicate that respondents agreed the existence of conflicts and the institutions they report conflicts on water with NAWASCO and Water project committees having the most cases of unresolved water conflicts. The data illustrates the presence of water related conflict in Upper Ewaso Ng'iro River Sub Basin in Kenya with various causes outlined explicating the unresolved conflicts (Kiteme, 2020;Lanari et al, 2018;Shao et al, 2017). Results agree with previous studies that rapidly increasing water demand as a result of rapid population growth; land use changes along rivers and wetlands have the potential to trigger repetitive conflicts (Daniel and Barreteau, 2015;Habiyakare and Zhou, 2015).…”
Section: Resultssupporting
confidence: 87%
“…Results in Table 3 indicate that respondents agreed the existence of conflicts and the institutions they report conflicts on water with NAWASCO and Water project committees having the most cases of unresolved water conflicts. The data illustrates the presence of water related conflict in Upper Ewaso Ng'iro River Sub Basin in Kenya with various causes outlined explicating the unresolved conflicts (Kiteme, 2020;Lanari et al, 2018;Shao et al, 2017). Results agree with previous studies that rapidly increasing water demand as a result of rapid population growth; land use changes along rivers and wetlands have the potential to trigger repetitive conflicts (Daniel and Barreteau, 2015;Habiyakare and Zhou, 2015).…”
Section: Resultssupporting
confidence: 87%
“…Winter irrigation occurs during this period. Previous works indicated that high‐frequency HD events, which can cause insufficient irrigation in winter, commonly decrease soil water storage and subsequently increase drought risks in spring (Campos et al, ; Shao et al, ). The sum of ED, HD, MD, and LD event frequencies totals 35% during March–August, which composes the primary spring and autumn irrigation periods.…”
Section: Resultsmentioning
confidence: 99%
“…The unreasonable development and excessive exploitation of the water resources has led to a serious decrease in the ground water storage. Precipitation is the main recharge source of surface water in this area [41,42]. Precipitation has a certain dilution effect on the concentration of river pollutants in the rainy season.…”
Section: Temporal and Spatial Variation In Nitrogenous Speciesmentioning
confidence: 99%
“…Sampling site F10 was located in a typical intensive agricultural area, and the application of nitrogenous fertilizer and ammonia fertilizer were the major factors for the increase in NH4 + -N and NO3 − -N concentrations. At the same time, the groundwater resources in the AR also reduced the nitrogen concentration by recharging the surface water [41]. The results of this study can be interpreted as the fact that the agricultural land is near the river channel, and the fluctuation of water quality is more sensitive with the changes in land use types or geological conditions, while the On the whole, the mean concentrations of TN and NH 4 + -N increased with the flow direction in the IR and UR.…”
Section: Temporal and Spatial Variation In Nitrogenous Speciesmentioning
confidence: 99%